2017
DOI: 10.1016/j.otsr.2016.09.026
|View full text |Cite
|
Sign up to set email alerts
|

Cadaver study of anatomic landmark identification for placing ankle arthroscopy portals

Abstract: IV, cadaver study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…In 22% (4/18), the arthroscope was in direct contact with the neurovascular bundle. 9 Scheibling et al 19 performed anterocentral portal placement in cadaveric ankles with and without ultrasonography and reported distances between the arthroscope and the anterior neurovascular bundle of 6.1 and 3.7 mm, respectively. However, Buckingham et al 2 found a mean distance of 0.7 mm for the artery with direct contact of the arthroscope in 90% and a 1.1-mm mean distance for the DPN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 22% (4/18), the arthroscope was in direct contact with the neurovascular bundle. 9 Scheibling et al 19 performed anterocentral portal placement in cadaveric ankles with and without ultrasonography and reported distances between the arthroscope and the anterior neurovascular bundle of 6.1 and 3.7 mm, respectively. However, Buckingham et al 2 found a mean distance of 0.7 mm for the artery with direct contact of the arthroscope in 90% and a 1.1-mm mean distance for the DPN.…”
Section: Discussionmentioning
confidence: 99%
“… 26 Moreover, ultrasonography for portal placement might decrease the risk for iatrogenic injuries. 19 …”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported a full-thickness injury to the extensor hallucis longus tendon by the anterior portal when ultrasonography was not used preoperatively [13]. Their study, however, found no cases of iatrogenic injury when preoperative ultrasonography was used.…”
Section: Discussionmentioning
confidence: 99%
“…We work with a classic 2-portal endoscopic approach: 1 posterolateral portal for the camera and 1 posteromedial portal for the instruments 9,10 (Fig 3). Performing dissection using the ArthroCare Super Turbovac 90 wand handpiece (Smith & Nephew Endoscopy, Andover, MA), we visualize the posterolateral tubercle of the talus and the subtalar joint.…”
Section: Surgical Techniquementioning
confidence: 99%